Internet-delivered emotional awareness and expression therapy for somatic symptom disorder: one year follow-up - Hallberg, Henrik; Maroti, Daniel; Lumley, Mark A.; Johansson, Robert (Frontiers in Psychiatry, 2025)
ObjectiveWe examined whether the treatment effects from a previous RCT of Internet-delivered Emotional Awareness and Expression Therapy (I-EAET) for somatic symptom disorder were maintained 12 months after treatment.Method12-month assessments of self-reported somatic symptoms, pain severity, and several secondary outcomes were compared with baseline and post-treatment levels within the I-EAET condition only, given that the waitlist control condition had already received treatment. Twenty-eight out of the original 37 participants (76%) in the I-EAET condition provided follow-up data.ResultsThe beneficial effects of I-EAET on somatic symptoms observed at post-treatment were maintained at the 12-month follow-up (d = -0.22, 95% CI: -0.72 to 0.28), as well as for pain intensity (d = -0.02, 95% CI: -0.52 to 0.48). From pre-treatment to 12-month follow-up, there was a medium effect on somatic symptoms (d = 0.74, 95% CI 0.23 to 1.24), and a small, non-significant effect for pain intensity (d = 0.43, 95% CI -0.06 to 0.93). Response rates (at least 50% symptom reduction) at 12-month follow-up were 25% for somatic symptoms, and 12% for pain intensity.ConclusionI-EAET seems to have positive long-term effects for somatic symptom disorder. Larger studies with controls and comparisons to other treatments are needed.